PEMANFAATAN MEDIA SOSIAL DALAM STRATEGI PEMASARAN DI SEKOLAH SKYE DIGIPRENEUR - ridwan, ridwan ramadi (STAI Kuala Kapuas, 2025)
This research examines the use of social media in marketing strategies at Skye Digipreneur School. The aim of the research is to determine strategies for using social media, the types of social media used, as well as supporting and inhibiting factors in using social media as a marketing strategy in the school. The research method used is descriptive qualitative. Data was collected through observation, interviews and documentation studies. Data analysis was carried out interactively through data reduction, data presentation, and drawing conclusions. The research results show that Skye Digipreneur School utilizes various social media platforms such as Facebook, Instagram, Twitter, and YouTube in its marketing strategy. The strategies implemented include creating interesting and relevant content, active interaction with the audience, and consistency in publications. The main supporting factors are the ease of access and wide reach of social media, while the challenges faced include the need for content consistency and professional management of interactions. This research provides insight into how educational institutions can optimize the use of social media in their marketing strategies, as well as recommendations for overcoming emerging challenges.